Management of scrotal and penile lymphedema – physiotherapist experience: A case series - Daptardar, Anuradha A; Janavlekar, Mrunali Ganesh; Mahajan, Sarika G (Indian Journal of Case Reports, 2025)
Scrotal and penile lymphedema (SPL) is one of the complications of urogenital cancer treatment. Presenting here with a case series of three patients who were referred to the physiotherapy department for SPL management. Although SPL is routinely treated surgically, there are no recommendations for the assessment of SPL. Hence, in our case series, assessments were done pre- and post-intervention using Modified Justine Whitaker’s pouch measurement for girth difference and genital lymphedema score for identifying symptoms. The gold standard management of lymphedema is complete decongestive therapy (CDT), which includes skin care, multilayered lymphedema bandaging with short-stretch bandages, manual lymphatic drainage, exercises, and a compression garment. In this case series, CDT was administered by modifying the bandages; Coban 2 and finger bandages were used for SPL. Coban 2 bandages are self-adhesive bandages that fix securely and firmly around the waist and genitals without causing slippage and can be left for 2–3 days or till it gets loosened. Interventions were done for 5 days. Physiotherapy approaches using the principles of CDT are beneficial and effective without subjecting patients to surgical assaults. Clinicians and physiotherapists should be made aware of the well-established conservative management of SPL, which is poorly practiced due to embarrassment, taboo, and fear.